Global Scenario of Radiation in Cancer Risk: A Review - Pandey, Govind (International Journal of Pharmaceutical & Biological Archive, 2010)
Emission of energy from any source is known as ‘radiation’. High frequency radiation, e.g., ionizing radiation and ultraviolet (UV) radiation may cause genetic damage, leading to cancer. The ionizing radiations include x-rays, γ-rays, cosmic rays and particles given off by radioactive materials, such as α and β particles, protons and neutrons. Radiant energy (UV rays of sunlight, ionizing electromagnetic or particulate radiation) induced the neoplasm (cancer) in both human beings and experimental animals. The ionized molecules are unstable and quickly undergo chemical changes, thereby forming the ‘free radicals’ that can damage the DNA molecule or other molecules around it. Hence, the ionizing radiations can cause mutation (change) in a cell’s DNA, resulting into cancer. Thyroid gland and bone marrow are most sensitive to radiations; while kidney, bladder and ovary are least affected. Some forms of leukemia (bone marrow cancer) appear to be the most common radiation-induced cancers. The atomic blasts in Japan showed that high-dose radiation increases the risk of developing several cancers, including leukemia. Breast cancer can be developed in elderly women by a much more extensive use of personal computers (more than 3 hours a day), mobile telephones, TV sets and other household electrical appliances. Children appear to be twice as sensitive as adults to the leukemia-causing effects of radiation, and unborn children exposed to radiation in the uterus are even more sensitive. The breast cancer risk is more than twice as high as normal; however, the risk of developing lung cancer is 50% higher and the risk for multiple myeloma is more than twice as high as in the general population. The radiation therapy at high doses can cause DNA mutations in cells that survive the radiation, which may lead to a second primary cancer. Of all the types of non-ionizing radiations, only UV rays are cancer-causing agents. The most skin cancers are a direct result of sunlight exposure as sun is the major source of UV radiation.